1985
DOI: 10.1104/pp.78.3.555
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Pathways of Methionine Metabolism and Their Regulation in Lemna

Abstract: Individual rates of metabolism of the sulfur, methyl, and 4-carbon moieties of methionine were estimated in Lemna paucicostata Hegelm. 6746 The known major pathways for metabolism of methionine in the great majority of plant tissues not evolving large amounts of ethylene are summarized in Figure 1 (reactions a through k). Studies focused on the pathway for net methionine formation (Fig. 1, ---) have clearly demonstrated that this process occurs via transsulfuration ( 12), is subject to feedback control at cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 16 publications
(32 reference statements)
2
83
0
Order By: Relevance
“…It has been suggested that, under normal conditions, the bulk of methionine turnover is involved in these reactions (4). The massive diversion of methionine to ethylene, ACC, and MACC synthesis following TDZ treatment (Table V) could have a dramatic effect on many of these critical metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that, under normal conditions, the bulk of methionine turnover is involved in these reactions (4). The massive diversion of methionine to ethylene, ACC, and MACC synthesis following TDZ treatment (Table V) could have a dramatic effect on many of these critical metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…After 3 h of incubation in the dark, groups of 10 discs were transferred to flasks containing 1 ml of the inhibitor solution. The flasks were sealed, incubated in the dark (27 ± 1°C), and the ethylene content of the flasks was determined after 4 increase in total EFE activity 1 and 2 d post-treatment. The large response to exogenous ACC by these tissues suggested that endogenous levels of this substrate were in no way saturating.…”
Section: Table IV Effects Of Various Inhibitors On Tdz-induced Ethylenementioning
confidence: 99%
“…The pellet was extracted with 3.9 mL methanol:chloroform (2: 1), while the small residue resulting from evaporation of the original supernatant fluid was extracted with a further 0.9 mL of methanol:chloroform (2: 1). After centrifugation, the two supernatants were combined and separated into methanol-water soluble and chloroform-methanol-soluble fractions (3). The two pellets were combined by transfer of the smaller one with methanol washes.…”
Section: Methodsmentioning
confidence: 99%
“…SAM is used in a wide variety of biological reactions and is the major hub of Met metabolism (Shen et al, 2002;Martínez-López et al, 2008). Over 80% of the Met is metabolized into SAM, of which 90% is used for transmethylation reactions (Giovanelli et al, 1985). SAM, as a universal methyl group donor, participates in numerous enzyme-catalyzed reactions.…”
mentioning
confidence: 99%